An electric power generation improvement for small Savonius wind turbines under low-speed wind - Kwanjai Nachaiyaphum; Chonlatee Photong (Institute of Advanced Engineering and Science, 2023)
Savonius wind turbines have advantages of self-rotating at low speed wind, high starting torque, and less noise generation. However, they have low electric power generation capacity. This paper presents electric power generation improvement for small Savonius wind turbines when operating at low-speed wind of 1-6 m/s by using optimal Bach-type blades, twist blades and a wind tunnel. The turbine prototypes with the optimum diameter and height of 32 cm were developed with 3 different blade types: conventional semicircular blades, Bach-type blades and twisted 15° blades and a wind tunnel. The experimental results showed that the Savonius wind turbine with Bach-type generated highest electric voltage, which was 19.3% and 7.6% higher compared to conventional blades and twisted 15° blades. The additional wind tunnel could improve electric power generation efficiency by approximately 21.4% compared to the turbines without the tunnels.